Elucidating the mechanisms underlying PCBM enhancement of CH3NH3PbI3 perovskite solar cells using GIXRD and XAFS. Issue 6 (22nd January 2020) - Liu, Bing; Cui, Rongli; Huang, Huan; Guo, Xihong; Dong, Jinquan; Yao, Huanli; Li, Ying; Zhao, Dangui; Wang, Jiahao; Zhang, Jing; Chen, Yu; Sun, Baoyun
Abstract : In this study, the stability mechanism of the optimized methyl ammonium lead triiodide (CH3 NH3 PbI3, MAPbI3 )/[6, 6]-phenyl-C61 -butyric acid methyl ester (PCBM) perovskite active layer upon exposure to moisture, light, and heating was investigated. Abstract : In this study, the stability mechanism of the optimized methyl ammonium lead triiodide (CH3 NH3 PbI3, MAPbI3 )/[6, 6]-phenyl-C61 -butyric acid methyl ester (PCBM) perovskite active layer upon exposure to moisture, light, and heating was investigated. For the first time, the existence of high-valence lead arising from PCBM is confirmed by X-ray absorption fine spectroscopy (XAFS) based on synchrotron radiation, which helps to form stronger Pb–I bonds and facilitate carrier transport. Moreover, the degree of disorder of perovskites and the [PbI6 ] 4− octahedral distortion are significantly improved, as well as the crystallization both on the surface and in the bulk. The result of this study provides a fundamental understanding of the functions of additives with electron-withdrawing properties ( e.g., PCBM) in perovskite materials and could specifically be extended to systematically design and fabricate high-efficiency and stable solar cells.